O riso: teorias e práticas criativas - Allan, Monica Pinheiro (2018)
Laughter is studied world-wide by diverse areas that have somehow tried to justify and analyze it, both in comedy and in the specificity of humor - separately. Henri Bergson, Sigmund Freud and Mikail Bakhtin are among the most influential theorists of the early twentieth century. Arthur Koestler presents, however, his own theory in Act of Creation (1964), one of the most complete works on the subject. The superior and the inferior of the Greek dramaturgical purposes, as well as the influence of their myths and rites are presented in the importance of the body and its moods. Discussions find historical roots in George Minois (2003), relational spheres in the ontological proposal of Peter Sloterdijk, when the animal is confronted with the sacred, or with the power. The animal that laughs is no longer alone, is what will show the laughter under the Amerindian multiperspectivism presented by Viveiros de Castro, with the rupture of anthropocentrism and from the neurological discoveries of Panksepp. Social function, psychosocial behavior, cultural mediation of times, psychogenesis, cynicism are some of the spheres of thought and humor that perhaps can be mapped in the discourse of creative theories and practices about laughter in complex and Brazilian ways. To put this hypothesis under analysis, some concepts of Peircian semiotics will be selected as fundamental keys to the analysis of laughter in the Porta dos Fundos language